2020
DOI: 10.1111/tesg.12436
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19, Virtual Church Services and a New Temporary Geography of Home

Abstract: The COVID‐19 pandemic and subsequent lockdown measures implemented by the United Kingdom government from 23 March 2020 led to unprecedented adaptations from individuals and communities including places of worship, their clergy and congregations. This paper through a multi‐disciplinary dialogue between human geography and theology explores the interrelations between place, space and the spiritual. It identifies the bricolage mechanisms that were developed rapidly by churches to shift towards providing virtual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 33 publications
1
40
0
11
Order By: Relevance
“…Bahkan, perayaan Natal yang menjadi momen spesial dilaksanakan tidak seperti biasanya. Para pemuka agama Kristen melakukan prosesi peribadatan di gereja dan diikuti secara daring oleh jamaah, bahkan di rumah-rumah dilakukan ibadah yang dikenal dengan "gereja rumah" (Bryson, Andres, & Davies, 2020;Ering, 2020). Pola beribadah seperti ini di satu sisi memang tetap menunjukkan tingginya kesalehan umat sebagai penganut agama yang taat, namun di sisi lain terdapat banyak sesuatu yang hilang karena adanya pembatasan-pembatasan dalam pelaksanaannya.…”
Section: Pendahuluanunclassified
“…Bahkan, perayaan Natal yang menjadi momen spesial dilaksanakan tidak seperti biasanya. Para pemuka agama Kristen melakukan prosesi peribadatan di gereja dan diikuti secara daring oleh jamaah, bahkan di rumah-rumah dilakukan ibadah yang dikenal dengan "gereja rumah" (Bryson, Andres, & Davies, 2020;Ering, 2020). Pola beribadah seperti ini di satu sisi memang tetap menunjukkan tingginya kesalehan umat sebagai penganut agama yang taat, namun di sisi lain terdapat banyak sesuatu yang hilang karena adanya pembatasan-pembatasan dalam pelaksanaannya.…”
Section: Pendahuluanunclassified
“…Церкви ще до пандемії швидко розвивались у напрямку надання віртуальних церковних послуг, але все ж це була не постійна практика християнських конфесій (Bryson, Andres, Davies, 2020). Проте, через кризу Covid, більшість церков змушені переходити у мережу Інтернет для зв'язку з вірянами (Geoffrey, 2020 (Pennebaker, Boyd, Jordan & Blackburn, 2015).…”
Section: Religious Communication In Times Covid-19: Psycholinguistic unclassified
“…Other scholars explored the modifications to religious rites and new approaches introduced by churches during the pandemic (Bryson et al 2020;Bawidamann et al 2020). Kim (2020) concluded that the transition to 'contactless' worship services had already taken place and had been accepted without being subject to the scrutiny of public debate.…”
Section: Introduction and The State Of The Artmentioning
confidence: 99%